ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL DALAM PEMBERIAN KREDIT PADA KOPERASI PEGAWAI REPUBLIK INDONESIA “GURU” SUMBERMANJING WETAN - Hendri Kurniawan; Moh. Amin; Siti Aminah Anwar (Universitas Islam Malang, 2022)
The accounting information system and the internal control system are a unity that is equally binding into two inseparable parts. Therefore, accounting information systems and internal control systems are two things that are needed and important, especially in financial institutions for the process of implementing credit. An accounting information system and internal control system can support company activities to run more effectively and efficiently. In financial institutions, the use of credit is not as expected, there are many problems that must be corrected, one of which is often non-performing loans, namely bad loans. The purpose of the research that is expected by the researcher is to find out regarding the application of accounting information systems and internal control systems in the employee cooperatives of the Republic of Indonesia